COMPARISON OF THE EFFICACY (IN TERMS OF STONE EXPULSION) OF TAMSULOSIN VERSUS NIFEDIPINE IN DISTAL URETERIC STONE - Mudassar Saeed Pansota; Sharmeen Shafqat; Shafqat Ali Tabassum et al. (Journal of University Medical & Dental College, 2019)
ABSTRACT: INTRODUCTION: In western prosperous countries, a great research has been done on these two medicines in urolithiasis. Extent of disease is varying from developing countries to developed countries, specially due to late identiﬁcation of diseases, late in examination which enhances the consequences of disease in ureteral stone or in any other disease. OBJECTIVES: To compare the eﬃcacy (in terms of stone expulsion) of tamsulosin versus nifedipine in victims with distal ureteral stone. MATERIAL AND METHOD: All of 86 patients with distal ureteric stone, 20 to 50 years of both genders were included. Patients with proximal ureteric stricture, gross hydronephrosis, previous ureteral surgery and solitary kidney were excluded. After informed, written consent, all selected cases were divided in two groups by lottery method. In group A patients, tamsulosin was given while in group B patients, nifedipine was given. All patients were followed weekly by the researcher till 4 weeks and ultrasonography in both groups was done by the one consultant radiologist for evaluation of eﬃcacy. RESULTS: Mean age was 32.29 ± 6.81 years. Out of these 86 patients, 53 (61.63%) were male and 33 (38.37%) were females with. Mean size of stone was 6.69±1.49 mm. Stone expulsion was seen in 37 (86.05%) patients in group A (tamsulosin group) and 25 (58.14%) patients in group B (nifedipine group) with p-value of 0.004. CONCLUSION: This survey concluded that eﬃcacy (in terms of stone expulsion) of tamsulosin is better as compared to nifedipine in distal ureteric stone